ответ:
объяснение:
f(x)=x³-27x
1) f `(x)=(x³-27x)`=3x²-27=3(x²-9)=3(x-3)(x+3)
2) f `(x)=0 при 3(x-3)(x+3)=0
x=3 v x=-3
+ - +
-
↑ ↓ ↑
f(x) - возрастает на (-∞; -3)u(3; +∞)
f(x)- убывает на (-3; 3)
2sin(x/2)=3sin²(x/2)
2sin(x/2)-3sin²(x/2)=0
sin(x/2) (2-3sin(x/2))=0
a) sin(x/2)=0
x/2=πk, k∈Z
x=2πk, k∈Z
b) 2-3sin(x/2)=0
-3sin(x/2)=-2
sin(x/2)=2/3
x/2=(-1)^n * arcsin(2/3)+πk, k∈Z
x=2*(-1)^n * arcsin(2/3)+2πk, k∈Z
ответ: 2πk, k∈Z;
2*(-1)^k*arcsin(2/3)+2πk, k∈Z.
2)
sin6xcosx+cos6xsinx=0.5
sin(6x+x)=0.5
sin7x=0.5
7x=(-1)^k*(π/6)+πk, k∈Z
x=(-1)^k*(π/42)+(π/7)*k, k∈Z
ответ: (-1)^k*(π/42)+(π/7)*k, k∈Z.
3)
3sinx+4sin(π/2+x)=0
3sinx+4cosx=0
=0
a) При у=-1/2
,
k∈Z;
b) При у=2
k∈Z.
ответ: k∈Z;
k∈Z.